Implementation of Project Based Learning on Students' Learning Interest and Understanding of Physics Concepts - Baharuddin, Nurhaliza; Usman; Khaeruddin, Khaeruddin; Setiawan, Trisno (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This research is pre-experimental research which aims to determine the increase in students' interest in learning and understanding of physics concepts after implementing the Project Based Learning (PjBL) model in physics subjects at SMA Negeri 1 Bone. This research uses One Group Pretest-Posttest Design. The class that was the research subject was class XI MIPA 2. The total number of research subjects was 33 students. Data were analyzed using Microsoft Excel 2010 using descriptive analysis and N-Gain test analysis to see the increase in students' interest in learning and understanding of physics concepts by applying the PjBL model to static fluid material. Based on the results of research on interest in learning physics, the average pretest score was 88.78 and the posttest score was 126.45, and for understanding physics concepts, the pretest score was 10 and for the posttest it was 16.12. For the results of the N-Gain test analysis on interest in learning physics, it was found that 33.33% was in the high category and 66.67% was found in the medium category. For the results of the N-Gain test analysis on understanding physics concepts, 33.33% were in the high category and 66.67% were in the medium category. This proves that before implementing the PjBL model, students' interest in learning and understanding of physics concepts were in the medium category. and after implementing the PjBL model, students' interest in learning and understanding of physics concepts is in the high category. The PjBL model can increase interest in learning and understanding of physics concepts in class XI MIPA 2 students at SMAN 1 Bone.